Evaluation of irrigation management in different stages of growth on the yield and water productivity in cowpea plant in field and model conditions - Faranak Baradaran-Hezaveh; Hossein Babazadeh; Ebrahim Amiri; Hossein Ebrahimi (Applied Water Science)
Abstract The research was conducted in order to evaluate the management of irrigation in different stages of growth on the yield of the cowpea plant using the DSSAT model. The experiment was conducted in the form of a randomized complete block design with three replications in the north of Iran during 2017 and 2018. The main treatments included irrigation with the management of 40, 60, 80, 100 and 120% of the plant’s water requirements (WRs), and the secondary treatment included irrigation in the vegetative, reproductive and complete stages (vegetative and reproductive). The outcomes indicated that the maximum yield of biomass, pod and seeds when supplying 100% of the water supply in 2017 was 4588, 3222 and 1005 kg/ha, respectively, in both vegetative and reproductive stages. In the interaction of year × WR × growth stages, the maximum water use efficiency based on yield of biomass, pod and seeds in 2018 were under irrigated conditions in the vegetative stage and in dry conditions with the average of 3.57, 2.37 and 0.75 kg/m3. The average values of water productivity components based on irrigation, irrigation and rainfall, evapotranspiration, transpiration and evapotranspiration and deep percolation altogether (WPI, WPI + R, WPET, WPT and WPETQ) was obtained as 0.61, 0.41, 0.39, 0.67 and 0.32 kg per cubic meter, respectively. The outcomes of evaluating DSSAT model showed that the values of RMSE and RMSEn in calibration conditions were, respectively, 130 kg/ha and 5.91% for biomass yield and 92 kg/ha and 12.62% for seed yield. In the validation conditions, these indicators were, respectively, 129 kg/ha and 5.29% for biomass yield and 73 kg/ha and 8.61% for seed yield. Based on the results, treating 100% of the water requirements in the vegetative and reproductive stages and with transpiration rate of 188 mm is suggested as suitable management for the studied area.